(untitled) - Davis, John C. (New York, 2002)
Thoroughly revised and updated, this new edition of the text that helped define the field continues to present important methods in the quantitative analysis of geologic data, while showing students how statistics and computing can be applied to commonly encountered problems in the earth sciences.
Keywords: Geology,Geology; Data processing,Statistical methods